Student Actions in the Learning Process of Indonesian Language Subjects and Their Implications for Improving Discussion Ability - Perida Roma Asi Siahaan; Erikson Saragih (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to analyze the types, functions and implications of students' speech acts, how the speech acts in speaking directly to students in class discussion activities in the Indonesian language subject at the Faculty of Economics, University of Prima Indonesia. This research method uses mequalitative descriptive research tode with a case study research design for Faculty students Economics of Prima Indonesia University, where the research data were collected using technique note, the method of observation, and listen. Sources of data were obtained from the results of students' speech acts in the learning process of discussing Indonesian Language courses. Types of speech acts used in discussion activities in the learning process are locus speech acts, illocutionary speech acts and perlocution speech acts. The speech act function used by students in discussion activities in the learning process is a locus speech act with a news function, with a question-speaking function, with a commanding speech function. Assertive illocutionary speech acts, directive illocutionary speech acts, expressive illocutionary speech acts, commissive illocutionary speech acts, and declarative illocutionary speech acts. Perlocutionary speech acts with the function of giving influence.